Kebudayaan dan Kearifan Lokal di Provinsi Jambi, Batak dan Jawa - Nasution, Imam Wahyudi; Wahyuni, Sri; Anwar, Kasful; A, Ansori (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Jambi Province has Malay background inhabitants. Have a very distinctive culture. Is his influence is the historical background of the jambi itself. There are various elements of culture that are felt to be necessary to preserve. As a form of awareness of the existing cultures of our homeland, in order to compete with foreign cultures. Jambi Malay culture contains a blend between Jambi Malay cultural elements including animism and dynamism, Buddhist Malay and Muslim Malay cultural elements. However it doesn’t take away from the original characteristics. Modern Batak history is influenced by two Heavenly religions, Islam and Christianity. Islam became stronger influence during the Priestly War, through the preaching activities carried out by the da’I from Minang. The expansion of the spread of Islam also once entered the area of North Tapanuli under the leadership of Tuanku Rao of West Sumatra, but not so successful. Islam is more developed among the Mandailing, the Old Desert, and parts of Angola. Javanese culture, as is known, that Javanese culture has been old throughout the Javanese have since then the Javanese have a progressive image by expressing their work through culture. Javanese culture is the reflection or expression of Javanese human nature that includes the will, ideals, ideas and spirit in achieving well-being, safety and happiness born inner life. Javanese culture was born and developed, initially, on the island of Java, an island more than 1,200 km long and 500 km wide when measured from its farthest ends. It is located on the southern edge of the Indonesian archipelago, approximately seven degrees south of the equator.